Analisis Awal Terhadap Dinamika Penanggulangan Cyberbullying di Ruang Digital Indonesia Dalam Perspeftif Hukum Pidana - Ahmad Ma’mun Fikri (UNES Law Review, 2023)
In Indonesia, the development of internet and social media usage has shown significant growth. In 2024, there are 204.7 million internet users in Indonesia, indicating an increase of approximately 2.1 million users from the previous year. Furthermore, internet penetration has reached 73.7% of the total population, while the number of active social media users stands at 191.4 million or 68.9% of the population, with an annual growth rate of 12.6%. This trend reflects the integration and importance of social media in the daily lives of Indonesian society, as well as the potential for misuse such as cyberbullying. This article focuses on an in-depth analysis of the dynamics of cyberbullying in Indonesia within the context of existing laws, with the primary aim of identifying gaps in current regulations and advocating for stronger legislation. The research method used is normative juridical. The study finds that cyberbullying in Indonesia is a serious issue affecting the mental health and well-being of individuals, particularly children and teenagers. Although regulated by the Electronic Information and Transactions Law (UU ITE), this regulation requires adjustments to be more specific and adaptive to technological developments. A holistic approach involving education, psychological support, and stakeholder collaboration is necessary to create a safe and supportive digital environment.